Museum Folkwang Essen : Gemälde : 19. und 20. Jahrhundert. - Museum Folkwang, Essen (Essen : Museum Folkwang, 1963)
Achenbach, Andreas ; Ahlers-Hestermann, Friedrich ; Baum, Paul ; Baumeister, Willi ; Bazaine, Jean René ; Beckmann, Max ; Bernard, Emile ; Böcklin, Arnold ; Bonnard, Pierre ; Braque, Georges ; Brücke, Wilhelm ; Bürkel, Heinrich ; Carus, Carl-Gustav ; Caspar-Filser, Maria ; Catel, Franz Ludwig ; Chagall, Marc ; etc.
boek